The value of verbal feedback in allocation decisions [online appendix and replication package] - Schmidt, Robert J.; Schwieren, Christiane; Vollmann, Martin (Universität, 2020)
Depending on the context at hand, people’s preference for receiving feedback might differ. Especially in allocation decisions that directly concern another individual, feedback from the affected person can have positive or negative value. We study such preferences in a laboratory experiment by eliciting the willingness-to-pay to receive or to avoid verbal feedback from subjects that were previously affected by an allocation decision. We find that most decision makers exhibit a positive willingness-to-pay for having control about whether feedback occurs or not. Specifically, decision makers that shared their endowment with the recipient equally revealed a positive willingness-to-pay for receiving, but not for avoiding feedback. By contrast, among decision makers that behaved selfishly, we identify both: subjects that were willing to pay for receiving and subjects that were willing to pay for avoiding feedback. The stated motivations indicate that curiosity, the desire to receive social approval and giving the recipient the chance to express his/her feelings are the main reasons for feedback acquisition, while shame and fear of negative feedback are the main reasons for avoidance.